A reorganização do espaço agrário de Júlio de Castilhos/RS: uma nova dinâmica através da lavoura empresarial da soja - Cargnin, Monica (2009)
The insertion of capital makes the territorial units organize and/or reorganize, as it happens in an unequal way in the space according to the demand of the market, considering the local, regional, national and international scales. Consequently, according to the technical degree and the presence of new economical factors, we get the spatial dynamics. At the present time, we have the increment of investments in technologies and capital for agriculture with the expansion of cultures turned to the external market. In the same way as managerial agriculture, the livestock seeks to be inserted in the modernization process through the genetic improvement of the flocks. In this perspective, this research is centered in the approach of the agricultural space of Júlio de Castilhos/RS. As general objective, the research seeks to understand the social economical dynamics, starting from the introduction of the productive chain of soy in the spatial organization/reorganization of Júlio de Castilhos. Specifically it was sought: (a) to identify the temporary mark of the soy culture insertion and its evolution in the occupation of the agricultural space of Júlio de Castilhos/RS; (b) to verify the existent relationship between the process of spatial removal of livestock culture and the insertion of the managerial farming of soy and, (c) to analyze the social, economical, technical and spatial transformations, starting from the introduction of the productive chain of soy, through the agricultural modernization and the improvement of infrastructure in the municipal district. For this analysis, it was combined techniques of collection of qualitative and quantitative data through primary and secondary sources. The interviews with the producers and the collection of primary data from IBGE and FEE composed the database, basis for the understanding of the space transformations. In the historical context, the genesis of this space cutting is tied to the distribution of lands, through the sesmarias donation, evidencing typical characteristics of this period, among them the traditional matrix, based on the extensive livestock. However, over the last decades, the primary section is going through significant changes in its productive process, mainly as to the agricultural production. The livestock, in this municipal district, is giving way to the managerial farming of soy. In Júlio de Castilhos, the livestock, considering the temporary scale in analysis, 1940 to 1995/96, presented significant decline, having its cattle reduced in about 50%. On the other hand, in the same period, the area of soy farming duplicated. This way, it can be affirmed that great part of the native fields with favorable topography for the development of the automated farming was transformed in farming. In parallel, the livestock, through genetic improvement, cultivation of pastures, and artificial insemination, seeks alternatives to compensate the area reduction given to the farming of soy. It is emphasized that the municipal district in question presents transformations in its productive space and, consequently, those modifications provoked reorganizations in the local economy, as in the urban and rural space, needing improvements in the infrastructure. It is also necessary to develop policies that help the dynamics of employment, structure the road network, among other dynamics forms that seek to insert the municipal district in the local/regional development.